2015
DOI: 10.1186/s12954-015-0088-4
|View full text |Cite
|
Sign up to set email alerts
|

Why the FUSS (Fentanyl Urine Screen Study)? A cross-sectional survey to characterize an emerging threat to people who use drugs in British Columbia, Canada

Abstract: BackgroundFentanyl-detected illicit drug overdose deaths in British Columbia (BC) recently increased dramatically from 13 deaths in 2012 to 90 deaths in 2014, signaling an emerging public health concern. Illicit fentanyl is sold as pills or powders, often mixed with other substances like heroin or oxycodone; reports from coroners suggested that fentanyl was frequently taken unknowingly by people who use drugs. This study aimed to assess the prevalence and characteristics of fentanyl use among clients accessing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 9 publications
6
87
1
Order By: Relevance
“…Of major public health concern is our finding that the majority of participants who reported FCH exposure had used it without knowing that their heroin was contaminated with fentanyl. To inform public health efforts that address FCH, future research should examine whether fentanyl contamination can be reliably identified prior to consumption (using rapid tests, for example) (Amlani et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Of major public health concern is our finding that the majority of participants who reported FCH exposure had used it without knowing that their heroin was contaminated with fentanyl. To inform public health efforts that address FCH, future research should examine whether fentanyl contamination can be reliably identified prior to consumption (using rapid tests, for example) (Amlani et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…By comparison, when used intravenously, fentanyl can cause life-threatening respiratory depression within two minutes (Green & Gilbert, 2016). The rapid onset of action and remarkable potency of fentanyl and its analogues can lead to dramatic central nervous system depression (Amlani et al, 2015) as well as potential chest wall rigidity (Burns, DeRienz, Baker, Casavant, & Spiller, 2016), that may further complicate overdose response.…”
Section: Overdose Response In the Synthetic Opioid Eramentioning
confidence: 99%
“…People who use opioids may prefer to use fentanyl as it is highly lipid-soluble, thus rapid-acting, and 40 times more potent at the opioid receptor than heroin, which results in fast onset euphoria and pain relief. Many PWID describe the experience as like heroin, but more intense (Amlani et al, 2015; Ciccarone, Ondocsin, & Mars, 2017; Macmadu, Carroll, Hadland, Green, & Marshall, 2017). Like heroin, fentanyl has a half-life of approximately 3-7 hours (Trescot, Datta, Lee, & Hansen, 2008), however, the duration of action of fentanyl is briefer, only 30-60 minutes for an intravenous injection, compared to 4-5 hours for heroin.…”
Section: Introductionmentioning
confidence: 99%
“…At present, IMF and NSO are causing an alarming spike in overdose deaths. This increase in fatalities seems partially due to the fact that many users are unknowingly consuming these compounds as adulterants in products sold as heroin, or as counterfeit pain killers (Amlani et al, 2015; DEA, 2016b). It is estimated that a single kilogram of NSO can be used to manufacture hundreds of thousands of counterfeit prescription tablets, which can produce millions of dollars in revenue for traffickers (DEA, 2016b).…”
Section: Introductionmentioning
confidence: 99%